African Countries in Quest for Information Sovereignty: Past and Present - Usacheva Veronica Vladimirovna (Ученые записки Института Африки Российской академии наук)
The article is devoted to the problem of information and cultural sovereignty and to the attempts of African countries to acquire and maintain it. The legacy of colonialism and neo-colonial practices of the former metropoles did not allow African countries to achieve information independence, without which the independence and sovereignty of the state as a whole are impossible. The newly independent states saw the role of the media primarily in creation, strengthening, and maintaining national unity, in the formation of a national cultural identity, and in combating colonialism. The article analyzes the peculiarities of media formation in Africa, the main focus of media activities after independence, the influence of Western countries and trans-national corporations on the cultural and informational sphere of African countries. Special attention is paid to the attempts of African countries to achieve a new fair information order. The era of liberalization in Africa led to contradictory results: the struggle for freedom of information continued as a struggle against internal authoritarianism, while the problem of domination of transnational information corporations and their products was obscured and faded into the background. Particularly in that period, the transformation of neocolonialism manifested itself: not only did the new neocolonialism become global, with a defined center of influence—it also denied states the right to implement sovereign information policies. The dominance of Western narratives persists in the African information space, often operating such terms as development, progress, modernization, international cooperation, human potential, and “strengthening the institutions of democracy,” but in reality, propagating the interests of the dominant powers, thus maintaining the new neocolonial agenda, cementing inequality and power imbalance.